2022
DOI: 10.3390/biology11091298
|View full text |Cite
|
Sign up to set email alerts
|

A High-Throughput Search for SFXN1 Physical Partners Led to the Identification of ATAD3, HSD10 and TIM50

Abstract: Sideroflexins (SFXN, SLC56) are a family of evolutionarily conserved mitochondrial carriers potentially involved in iron homeostasis. One member of the SFXN family is SFXN1, recently identified as a human mitochondrial serine transporter. However, little is known about the SFXN1 interactome, necessitating a high-throughput search to better characterize SFXN1 mitochondrial functions. Via co-immunoprecipitation followed by shotgun mass spectrometry (coIP-MS), we identified 96 putative SFXN1 interactors in the MC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(98 reference statements)
1
1
0
Order By: Relevance
“…In the fibroblasts of these patients, the aggregation of mitochondria, the accumulation of mtDNA, and an increase in free cholesterol were observed. These observations by Gunning et al were similar to those associated with ATAD3 cluster deletions reported by Desai et al [34], indicating that the protein resulting from the fusion of the ATAD3A and ATAD3C genes may be nonfunctional.…”
Section: Copy Number Variantssupporting
confidence: 80%
See 1 more Smart Citation
“…In the fibroblasts of these patients, the aggregation of mitochondria, the accumulation of mtDNA, and an increase in free cholesterol were observed. These observations by Gunning et al were similar to those associated with ATAD3 cluster deletions reported by Desai et al [34], indicating that the protein resulting from the fusion of the ATAD3A and ATAD3C genes may be nonfunctional.…”
Section: Copy Number Variantssupporting
confidence: 80%
“…Sideroflexin 1 (SFXN1), a human mitochondrial serine transporter, was also shown to interact with ATAD3A in MCF7 cells, a human breast cancer cell line, identified by coimmunoprecipitation followed by shotgun mass spectrometry (coIP-MS) (Figure 2 #6) [34]. The significance of this interaction is yet to be understood.…”
Section: Atad3a-protein Interactions and Functionmentioning
confidence: 99%